2018
DOI: 10.2147/ppa.s179465
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on the attitudes of patients with gastrointestinal cancer toward being informed of the truth

Abstract: ObjectiveThe aim of this study is to investigate the attitudes of hospitalized patients with gastrointestinal cancer toward being informed of the truth and to provide references for informing patients of their gastrointestinal cancer diagnosis.MethodsNine patients with gastrointestinal cancer were selected for this study by using a purposive sampling technique from a general surgery ward in a tertiary-level general hospital in Zhejiang Province from June 2016 to October 2016. Semi-structured, in-depth intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
2
6
0
Order By: Relevance
“…However, eight (8) respondents (three from the maternity ward cohort and five from each general surgical ward cohort) were traced to their homes and primary data on their lived experiences was collected. This choice is in line with a similar qualitative study by Yang et al (2018).…”
Section: Data Collection Sources Tools and Techniquessupporting
confidence: 58%
“…However, eight (8) respondents (three from the maternity ward cohort and five from each general surgical ward cohort) were traced to their homes and primary data on their lived experiences was collected. This choice is in line with a similar qualitative study by Yang et al (2018).…”
Section: Data Collection Sources Tools and Techniquessupporting
confidence: 58%
“…For the qualitative data, repeated replay was made to appreciate the information and make substantive meaning out of it, that is, content checking. This enabled the development of the appropriate thematic areas (Yang et al, 2018)…”
Section: Validitymentioning
confidence: 99%
“…Previous studies have shown that health care professionals should carefully select the appropriate time to inform patients of their diagnosis and actively meet patients' needs for personcentred information (Hakansson Eklund et al, 2019;Ibrahim et al, 2019;Larnebratt et al, 2019;Schildmann et al, 2013;Tariman et al, 2010;Yang et al, 2018). The findings of this study indicated that the next of kin felt mentally blocked, went into their own world and could not cope with the situation.…”
Section: Discussionmentioning
confidence: 71%
“…Honest communication is of great importance (Otutaha et al, 2019;Yang et al, 2018). Environments are perceived as very positive when relatives can share their experiences, obtain information and knowledge from healthcare professionals and be involved in patient care.…”
Section: Discussionmentioning
confidence: 99%